A 24-month cost and outcome analysis comparing traditional fronto-orbital advancment and remodeling with endoscopic strip craniectomy and molding helmet in the management of unicoronal craniosynostosis: A retrospective bi-institutional review. (June 2019) - Jivraj, B.A.; Ahmed, N.; Karia, K.; Menon, R.; Robertson, E.; Sodha, A.; Wormald, J.C.R.; O'hara, J.; Jeelani, O.; Dunaway, D.; James, G.; Ong, J.
Abstract: Introduction: Endoscopic strip craniectomy with helmeting (ESCH) has been shown to be a safe and efficacious alternative to fronto-orbital remodeling (FOR) for selected children with craniosynostosis. In addition to clinical factors, there may be economic benefits from the use of ESCH instead of FOR. Methods: A retrospective review of 23 patients with nonsyndromic unicoronal craniosynostosis (UCS) treated with FOR was carried out at Great Ormond Street Hospital (GOSH) for Children in London, UK. Secondary data were used for the ESCH cohort from a paper published by Jimenez and Barone (2013). Data were collected on surgical time, transfusion rates, length of hospital stay, adverse event rates, reintervention rates, and overall costs. Costs were categorized and then assigned to the appropriate data sets. Results: The mean age of patients undergoing FOR (vs. ESCH) was 17.4 mo (vs. 3.1 mo) with a mean surgical time of 234 min (vs. 55 min), mean transfusion volume of 221.6 mL (vs. 80.0 mL), mean transfusion rate of 14/23 (vs. 2/115), and a total immediate overnight stay of 3.13 days (vs. 97% next-day discharge). The FOR group had a higher adverse event rate (5/23 vs. 4/115, p =<0.005) and a higher number requiring extraocular muscle surgery (4/23 vs. 7/109, p =0.16). There was a substantial difference in overall costs between the two groups. Total variance cost for the FOR group was £7436.5 vs. £4951.35, representing a cost difference of £2485.15 over the 24-month study period. Conclusion: ESCH, in comparison to FOR, appears as a more economical method in the management of USC patients, as well as having clinical benefits including reduced adverse event rate and improved ophthalmic outcomes.